SECRECY CAPACITY AND SIGNAL ENHANCEMENT ANALYSIS USING RECONFIGURABLE INTELLIGENT SURFACES FOR SECURE LINE-OF-SIGHT B5G LINKS - Abdul Haseeb Minhas; Muhammad Ahmed Abbas; Syed Muhammad Talal Sherazi; Noor Eman Salaha; Malik Muhammad Zubair; Ahmad Raza (Spectrum of Engineering Sciences, 2025)
This work explores the application of Reconfigurable Intelligent Surfaces (RIS) in achieving physical layer security for next-generation wireless networks. As high-frequency 5G/6G communication systems gain popularity, providing secure and high-capacity links with rising eavesdropping threats is essential. We concentrate on maximizing the secrecy capacity and signal power at the authentic receiver (LR) while minimizing signal quality at possible eavesdroppers (Eve). A mathematical model is formulated to calculate the attainable rates and signal-to-noise ratios (SNRs) for RIS and non-RIS environments. Simulation results show that RIS strongly improves the quality of the signal at LR, resulting in up to 3.3× SNR improvement and a 200% increase in secrecy capacity over LoS transmission. In addition, the Signal Enhancement Ratio (SER) is maintained over a wide range of SNR values, verifying the stability of RIS-assisted communication. These results identify RIS as a promising technology for high-performance and secure wireless communications in beyond-5G (B5G) and 6G scenarios.